Simple tools and techniques for enterprise risk management - Chapman, Robert J. (Wiley, 2011)
Your business reputation can take years to build - and mere minutes to destroy. The range of business threats is evolving rapidly but your organization can thrive and gain a competitive advantage with your business vision for enterprise risk management. Trends affecting markets - events in the global financial markets, changing technologies, environmental priorities, dependency on intellectual property - all underline how important it is to keep up to speed on the latest financial risk management practices and procedures. This popular book on enterprise risk management has been expand.- Resumé vydavatel
"Reccommended by the Institute of Risk Management."
Keywords: rizikový management; riziko (ekonomie); rozhodování; risk management; risk (economic theory); decision making; elektronické knihy; monografie; electronic books; monographs